The effects of spironolactone in preventing bile duct ligation-induced hepatitis in a rat model - VELİOĞLU ÖĞÜNÇ, AYLİZ; ÇETİNEL, ŞULE; TETİK, ŞERMİN (Iranian Journal of Pharmaceutical Research, 2021)
Cholestasis is associated with the accumulation of bile acids and bilirubin in the hepatocytes and leads to liver injury. Pregnane X Receptor (PXR) coordinates protective hepatic responses to toxic stimuli, and this receptor was reported to stimulate bile secretion by increasing MRP2 expression. Since PXR activators were reported to be anti-inflammatory in the liver, PXR was proposed as a drug target for the treatment of chronic inflammatory liver diseases. We investigated the potential protective effect of spironolactone (SPL), an enzyme inducer, in hepatotoxicity induced by bile duct ligation in rats. Wistar Albino (250-300 g) rats were divided into the control group and the bile duct ligated (BDL) group. BDL group was divided into three subgroups; following BDL, for 3 days, the first group received propylene glycol (vehicle of SPL) (blinded), the second subgroup received spironolactone (SPL) (200 mg/kg oral), and the third subgroup received SPL for 3 days, starting 3 days after the bile duct ligation, in order to investigate if it has a healing effect after hepatitis had developed. The control group was sham-operated and received saline. At the end of the experiment, blood and tissue samples were collected. Serum TNF-α, NF-ĸB, bilirubin, IL-6 levels, ALT, AST, ALP activities and tissue MPO activity and oxidant damage increased after the bile duct ligation was significantly decreased following SPL administration. PXR and MRP2 activity showed an increase in the hepatocytes as a result of the treatment. In conclusion, it was observed that SPL administration significantly decreases liver inflammation and damage related to BDL. © 2021, Iranian Journal of Pharmaceutical Research. All rights reserved.
Keywords: Cholestasis; Inflammation; Multidrug resistance-associated protein 2; NF-ĸB; PregnanX receptor; Spironolactone